Alkitab sebagai Landasan Berpikir Kritis - Fransiska Angela Sampouw; Tonny Andrian Stefanus; Maria Titik Windarti (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
In today's life, humans are faced with various challenges. A mature way of thinking is needed. Critical thinking is one of the thinking processes that is qualified in seeing, reading, analysing and responding to situations and issues that require solutions. Critical thinking is the process of analysing, examining and formulating judgements based on deeper thinking in addressing matters that need to be revealed. In this study, using descriptive qualitative research methods through a library research approach. As a result, it was found that the purpose of critical thinking is to reveal the truth by attacking and eliminating everything that is wrong, to reveal the truth. In building a critical mind, humans need the right foundation. Both in terms of knowledge and religion. In research related to building critical thinking skills is through a religious approach, in this case the Christian faith. The Bible is the basis of Christian life. The Bible is the authoritative Word of God in Christian life. The Bible as the foundation of critical thinking reveals that building critical thinking skills requires: Wisdom; Transformation of the intellect; and Testing and Evaluating everything before it is accepted and applied in life.